Artesunate inhibits airway remodeling in asthma via the MAPK signaling pathway - Zhang, Mengyuan; Lin, Jiangtao; Zhang, Jingyuan; Zhao, Ruiheng; Wan, Jingxuan; Nong, Ying (Frontiers in Pharmacology, 2023)
Background: Artesunate (ART), is often used to treat malaria, a semi-synthetic water-soluble artemisinin derivative extracted from the plant Artemisia annua. In vivo and in vitro studies suggested it may help decrease inflammation and attenuate airway remodeling in asthma. However, its underlying mechanism of action is not elucidated yet. Herein, an attempt is made to investigate the ART molecular mechanism in treating asthma. Methods: The BALB/c female mice sensitized via ovalbumin (ova) have been utilized to establish the asthma model, followed by carrying out ART interventions. Lung inflammation scores by Haematoxylin and Eosin (H&E), goblet cell hyperplasia grade by Periodic Acid-Schiff (PAS), and collagen fibers deposition by Masson trichrome staining have been utilized for evaluating how ART affects asthma. RNA-sequencing (RNA-seq) analyses were performed to identify differentially expressed genes (DEGs). The DEGs were analyzed by Gene Ontology (GO) terms, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and Protein-Protein interaction (PPI) function analyses. Hub clusters were found by Cytoscape MCODE. Subsequently, Real-Time quantitative PCR (RT-qPCR) verified the mRNA expression profiles of DEGs. Finally, immunohistochemistry (IHC) and western blots have validated the relevant genes and potential pathways. Results: ART considerably attenuates inflammatory cell infiltration, mucus secretion, and collagen fibers deposition. KEGG pathway analysis revealed that the ART plays a protective role via various pathways including the mitogen-activated protein kinase (MAPK) pathway as one of them. Moreover, ART could alleviate the overexpression of FIZZ1 as revealed by IHC and Western blot analyses. ART attenuated ova-induced asthma by downregulating phosphorylated p38 MAPK. Conclusion: ART exerts a protective function in a multitarget and multi-pathway on asthma. FIZZ1 is a possible target for asthma airway remodeling. The MARK pathway is one of the key pathways by which ART protects against asthma.